PERBANDINGAN ASURANSI LAST SURVIVOR DENGAN PENGEMBALIAN PREMI MENGGUNAKAN METODE COPULA FRANK, COPULA CLAYTON, DAN COPULA GUMBEL - BRAMANTA, I GEDE DICKY ARYA; WIDANA, I NYOMAN; HARINI, LUH PUTU IDA; SUMARJAYA, I WAYAN (E-Jurnal Matematika; Vol 6 No 3 (2017), 2017)
This study examines about last survivor life insurance with return of premium for married couples with independent and dependent mortality model. By using Frank copula, Clayton copula, Gumbel copula and Indonesian Mortalita Table 2011, the impact of future life dependence on single premiums and annually premium is evaluated. Based on the calculation of premium with a 10 year contract for the insured parties aged 58 years and 55 years with interest rate used 6.5%, the value of insurance premium last survivor with return of premium is more expensive than without return of premium. The greater the dependency, the more expensive the price of the premium.